Rice bran extract supplement improves sleep efficiency and sleep onset in adults with sleep disturbance: A randomized, double-blind, placebo-controlled, polysomnographic study - Min Young Um (Nature Portfolio, 2019)
Abstract We previously reported that rice bran extract supplement (RBS) administration to mice decreased sleep latency and induced non-rapid eye movement (NREM) sleep via inhibition of the histamine H1 receptor. Based on this, we performed the first clinical trial to investigate whether RBS would be beneficial to subjects with disturbed sleep. We performed a randomized, double‐blinded, placebo‐controlled, 2-week study. Fifty subjects with sleep disturbance were enrolled and received either RBS (1,000 mg/day) or placebo. Polysomnography was performed, and Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale (ESS), and Fatigue Severity Scale were administered at the initiation and termination of the study. Compared with the placebo, RBS led to significant polysomnographic changes, including decreased sleep latency (adjusted, P = 0.047), increased total sleep time (P = 0.019), and improved sleep efficiency (P = 0.010). Additionally, the amount of stage 2 sleep significantly increased in the RBS group. When adjusted for caffeine intake, wakefulness after sleep onset, total wake time, and delta activity tended to decrease in the RBS group. RBS administration decreased ESS scores. There were no reported serious adverse events in both groups. RBS improved sleep in adults with sleep disturbance. Trial registration: WHO ICTRP, KCT0001893.